Task-Based Arabic Syntax Learning Design through STEM Integration - Anwar Sidik; Rizka Sari; Siti Kholifah; Gesta Lestari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This study aims to develop an Arabic syntax learning model that integrates Task-Based Language Teaching (TBLT) and STEM to improve students’ language skills and scientific literacy. The research used a Research and Development (R&D) method adapted from Borg & Gall, involving seven stages, including needs analysis, expert validation, and limited trials with 10 university students in the Arabic Language Education Program at ISQ Syekh Ibrahim. The learning model consists of six thematic units that integrate STEM themes into Arabic syntax topics such as jumlah ismiyyah, jumlah Fi’liyah, idhafah, and na’at, using TBLT stages: pre-task, task cycle, and language focus. Expert validation showed high feasibility (90%). Trial results indicated a significant improvement in students’ syntax achievement, with average scores increasing from 65.0 to 82.7, as well as higher motivation, collaboration, and critical thinking. Overall, the integration of TBLT and STEM made Arabic grammar learning more meaningful and contextual. The study concludes that the TBLT–STEM approach is effective in improving Arabic syntax learning outcomes at the university level.